Effectiveness of Simulation-Based Learning Media in The Understanding of Physics Concepts: A Literature Review - Basri, Nur Akhyar; Islamiyah, Muizzatul; Ardilla, Sarah Lutfiah; Irawan, Ivan Danar Aditya (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This study aims to evaluate the effectiveness of simulation-based learning media in enhancing conceptual understanding of physics at the senior high school level. The method used is a Systematic Literature Review (SLR) by adopting a systematic protocol for searching and selecting articles. Literature was retrieved from three main databases: Google Scholar, Semantic Scholar, and ScienceDirect. The analysis focused on 10 articles that met the inclusion criteria, namely: published between 2010–2024; used experimental methods with simulation media in physics education; had high school students as research subjects; and examined aspects of conceptual understanding. The review results show that simulation media is effective in presenting abstract and complex physics concepts in a visual manner that helps students understand the relationship between theory and everyday phenomena. Simulations also enable students to control variables, engage in independent exploration, and build stronger mental models. In addition, simulations have been proven to improve student performance in terms of recall, understanding, and analysis. However, there are some limitations, such as the lack of hands-on laboratory experience, the limited ability of simulations to represent real-world conditions, and minimal social interaction among students during the use of virtual media. Therefore, the use of simulation media should be integrated with other instructional approaches to optimize its effectiveness.